New versions of the BEAMDULAC code for high intensity ion beam dynamics investigation - Masunov, E.S.; Polozov, S.M. (Вопросы атомной науки и техники, 2006)
New versions of the BEAMDULAC code are described. Such code can be used for high intensity ion beam dynamics investigation in linear accelerators. New abilities of the code are presented and the code testing is observed. A code version for beam dynamics investigation in a beam transport channel is also discussed.